The year of the garden - Cheng, Andrea; Barton, Patrice, 1955- (Boston ; New York : Houghton Mifflin Harcourt, 2017)
"Follows perceptive, astute Anna as she strives to grow a perfect garden -- only to realize that the garden she grows with her new friend is more than good enough, weeds and all"--
Prequel to: The year of the book.
"A Junior Library Guild selection"--Jacket flap.
Keywords: Chinese Americans -- Juvenile fiction; Chinese Americans -- Fiction; Friendship -- Fiction; Gardening -- Fiction; Moving, Household -- Fiction; JUVENILE FICTION -- Nature & the Natural World -- Environment; JUVENILE FICTION -- Recycling & Green Living; JUVENILE FICTION -- Social Themes -- Friendship; Chinese Americans; Moving, Household -- Fiction; Chinese Americans -- Fiction; Friendship -- Fiction; Gardening -- Fiction